Realisasi Proses Transitivitas pada Pidato Shinzou Abe di Acara “Singapore Lecture” ke-33 - Mu'alim Nur Ahsan; Eri Kurniawan; Retty Isnendes (Journal on Education, 2024)
This research discusses how the transitivity process was realized in Shinzou Abe's speech at the 33rd "Singapore Lecture", using transitivity process analysis, it can be seen how Shinzo Abe as the leader of the country shows his attitude verbally in the international sphere, especially in this case countries ASEAN. Researchers used speech data taken from the archives of the Japanese Ministry of Relations, which was then broken down into sentences for analysis to find the dominant transitivity process. As a result, 223 data were obtained which were dominated by the behavioral transitivity process, amounting to 83 data or 37.22%. The discussion which was the main point in Shinzo Abe's speech was more focused on building cooperation and good relations with ASEAN countries.